Performance Persistence of Fixed Income Funds in Thailand - Raungsombut, Noppakoaw (Asian Administration and Management Review, 2019)
The objective of this research is to study the operational performance and persistence of fixed income funds in Thailand during 2008 - 2017. The results reveal that the rate of returns of most fixed income funds give the Underperforming for the case of not considering the risk factors and measuring the performance by Sharpe Ratio. However, when considering Riskadjusted Returns by using the Capital Asset Pricing Model (CAPM), the majority of fixed income funds are found to be able to generate little excessive returns (Alpha) with statistical significance. Besides, in studying the performance persistence of fixed income funds using the Winner-Winner, Winner-loser Persistence Test, the results of this research confirm the results of most researches on foreign fixed income funds that the performance of the Fixed Income Funds has the persistence at low to moderate level. This demonstrates the empirical results that fixed income funds are likely to continue to generate Poor Performance Persistence more than Good Performance Persistence.